Ireland : 2022 Article IV Consultation-Press Release; Staff Report; and Informational Annex. (IMF Staff Country Reports; Country Report ;, 2022)
Ireland's economy has rebounded strongly from the pandemic. GDP surpassed its pre-pandemic trend in 2021:Q4-one of the few euro area countries to do so. COVID-support measures have been appropriately unwound, and the fiscal position improved significantly. The financial sector weathered the pandemic crisis well and remains resilient. While the outlook is strong, uncertainty is substantial due to the indirect impacts of the war in Ukraine. Several pre-pandemic challenges remain: housing shortages, infrastructure, social and green investment gaps, and the need to strengthen multinational enterprises' inward linkages to broaden growth and make it more inclusive. There is also a need to address the Global Financial Crisis (GFC) legacy effects on the financial system and tackle the factors contributing to high lending interest rates.